Comet: An open‐source MS/MS sequence database search tool. Issue 1 (4th December 2012) - Eng, Jimmy K.; Jahan, Tahmina A.; Hoopmann, Michael R.
<x xml:space="preserve">Abstract</x> Proteomics research routinely involves identifying peptides and proteins via MS/MS sequence database search. Thus the database search engine is an integral tool in many proteomics research groups. Here, we introduce the Comet search engine to the existing landscape of commercial and open‐source database search tools. Comet is open source, freely available, and based on one of the original sequence database search tools that has been widely used for many years.